Separate to operate: control of centrosome positioning and separation - Agircan, Fikret Gürkan; Schiebel, Elmar; Mardin, Balca (Philosophical transactions. Series B, Biological sciences, 2014)
The centrosome is the main microtubule (MT)-organizing centre of animal cells. It consists of two centrioles and a multi-layered proteinaceous structure that surrounds the centrioles, the so-called pericentriolar material. Centrosomes promote de novo assembly of MTs and thus play important roles in Golgi organization, cell polarity, cell motility and the organization of the mitotic spindle. To execute these functions, centrosomes have to adopt particular cellular positions. Actin and MT networks and the association of the centrosomes to the nuclear envelope define the correct positioning of the centrosomes. Another important feature of centrosomes is the centrosomal linker that connects the two centrosomes. The centrosome linker assembles in late mitosis/G1 simultaneously with centriole disengagement and is dissolved before or at the beginning of mitosis. Linker dissolution is important for mitotic spindle formation, and its cell cycle timing has profound influences on the execution of mitosis and proficiency of chromosome segregation. In this review, we will focus on the mechanisms of centrosome positioning and separation, and describe their functions and mechanisms in the light of recent findings.